Why and how superpowers replace each other? (Salam International Academic Journal, 2020)
The international system has great impact on countries domestic and ‎foreign policies. World powers focus their foreign policy on the ‎international system so that they can achieve their national goals and ‎even sometimes they have to apply the international system to their ‎domestic policies. The top global powers for having greater impact on ‎others and to meet their national goals as far as they can, try to lead ‎international system, which increases competition and conflicts among ‎the world powers. This struggle resulted in the fall and rise of super ‎powers throughout the history. This article has attempted to discuss ‎this process. The rise and fall of super powers have similarities and ‎differences have been addressed as well. Similarly, the views and ‎perceptions of America’s political Science Professor on the transfer of ‎power from west to east or fall of America’s superiority have been also ‎addressed. These views or opinions have their own followers and ‎opponents, whose reasoning has been mentioned. At the end, this article ‎explains that despite the similarities and differences of the transition of ‎super power in the history of new states, lagging behind the needs of the ‎time has accelerated the process of the fall of super powers. ‎‎ Despite the superiority of America in terms of material strength, ‎Professor Norman Grin believes that(root of the collapse of America and ‎the escalation of the violence in the “wealth without work, pleasure ‎without conscience, knowledge without character, commerce without ‎morality, science without humanity, worship without sacrifice and ‎politics without principles) the lack of consciousness, humanity, ‎morality and ethics can led America to leave the throne of superiority in ‎the near future, likewise the way to fill this vacancy also discussed. ‎What this article believes about the future of international system is that ‎one or few countries to lead the international system are difficult for ‎countries, whilst the international community cannot survive without a ‎system.  So leadership of the future system should be given to regional or ‎international organizations that are truly independent of the will of the ‎states.‎